British Employers' Confederation document on the Beveridge Report (letter) - Baylay, A. C.
1943-02-01 1943 1940s 2 pages PHOENIX CHAMBERS, COLMORE ROW, BIRMINGHAM, 3 TELEPHONES: CENTRAL 6067, 6068, 6069 TELEGRAMS: "SAFEGUARD, BIRMINGHAM" 1st February 1943 FILE C216 RECD 2-FEB 1943 ANSD. 2.2.43 H.M. Piper Esq., British Employers' Confederation, Millbank House, 2, Gt. Peter Street, Westminster, London, S.W.1. Dear Piper, I was sorry not to have been able to have been at the Confederation meetings on Friday. I do not know yet what decisions you came to. I, however, want to say that I think the Confederation document on the Beveridge Report is extremely good, and is a very clear appreciation of the position. On the lighter side, I enclose you a copy of a little poem I got hold of the other day, which also puts the position very nicely. Yours sincerely, A.C. Baylay Enclosure. 200/B/3/2/C216/5/61